Partial Shading in Building Integrated PV System: Causes, Effects and Mitigating Techniques - Zainal Salam; Zulkifli Ramli; Jubaer Ahmed; Muhammad Amjad (Institute of Advanced Engineering and Science, 2015)
This paper is aimed to provide a holistic understanding on the issues related to partial shading: its causes, the theoretical and physical reasons behind it, its implications on the BIPV system. Furthermore the possible mitigation techniques using the software (MPPT) and hardware solutions are discussed. Finally an example is given to illustrate the impact of partial shading and the economic benefits of employing various partial shading mitigation techniques into the BIPV system To aid the unfamiliar readers in this subject, a brief but comprehensive overview of important PV concepts are also given.